Fetal brain sparing in a mouse model of chronic maternal hypoxia. Issue 6 (June 2019) - Cahill, Lindsay S; Hoggarth, Johnathan; Lerch, Jason P; Seed, Mike; Macgowan, Christopher K; Sled, John G
Hypoxic stress is a common occurrence during human pregnancy, yet little is known about its effects on the fetal brain. This study examined the fetal hemodynamic responses to chronic hypoxia in an experimental mouse model of chronic maternal hypoxia (11% O2 from E14.5 to E17.5). Using high-frequency Doppler ultrasound, we found fetal cerebral and ductus venosus blood flow were both elevated by 69% and pulmonary blood flow was decreased by 62% in the fetuses exposed to chronic hypoxia compared to controls. This demonstrates that brain sparing persists during chronic fetal hypoxia and is mediated by "streaming, " where highly oxygenated blood preferentially flows through the ductus venosus towards the cerebral circulation, bypassing the liver and the lungs. Consistent with these changes in blood flow, the fetal brain volume measured by MRI is preserved, while the liver and lung volumes decreased compared to controls. However, hypoxia exposed fetuses were rendered vulnerable to an acute hypoxic challenge (8% O2 for 3 min), demonstrating global blood flow decreases consistent with imminent fetal demise rather than elevated cerebral blood flow. Despite this vulnerability, there were no differences in adult brain morphology in the mice exposed to chronic maternal hypoxia compared to controls.